Development of Primary School Level P5 Project Module Based on Local Wisdom Hiem (Aceh Language Puzzle) - Sulhan Yus; Zulfatmi, Zulfatmi; Hayati, Hayati; Muji Mulia; Silahuddin, Silahuddin (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2025)
The project to strengthen the student profile of Pancasila is one of the flagship programs introduced in the Merdeka Curriculum, which raises various themes, including the theme of local wisdom. In the implementation of the P5 local wisdom theme, its application often ignores the local wisdom in the region itself, this happens because there is no local wisdom P5 project module in a region. The richness of regional culture in the archipelago is very abundant and should be preserved to young genersai, so as not to be lost in the current of globalization. The purpose of this study was to determine the initial needs for the development of P5 project modules on the theme of local wisdom based on Aceh hiem. This study uses the research and development (RnD) method with the ADDIE model, at the needs analysis stage, data collection techniques through questionnaires, interviews, and observations. Based on the analysis of the needs of schools, teachers and students, this study concludes that the development of a P5 project module on the theme of local wisdom based on Aceh hiem is needed to facilitate teachers in implementing P5 on the theme of local wisdom; help preserve Acehnese traditional literature, namely hiem, so that it is alive and sustainable in the Acehnese community; preserve the richness of Acehnese vocabulary so that the younger generation is proud and loves to speak in Acehnese language as a wealth of Aceh and the archipelago. The conclusion of this research is an optimistic step in developing an effective, valid and practical P5 project module for teachers to implement in the implementation of P5 at the elementary school level.